Cardiovascular syphilis treated with transcatheter aortic valve replacement. Issue 4 (31st January 2022) - Xiao, Bowen; Liu, Lulu; Peng, Ying; Kang, Zhefeng; Guo, Yingqiang
Abstract: Cardiovascular syphilis presented with concomitant aortic regurgitation (AR) and left coronary ostial stenosis is rare, usually treated with on‐pump aortic valve replacement and coronary artery bypass graft. We report a critical case of AR and left coronary ostial stenosis due to cardiovascular syphilis treated with emergent salvage transcatheter aortic valve replacement and percutaneous coronary intervention.